Genome-wide RNA-Seq identifies TP53-mediated embryonic stem cells inhibiting tumor invasion and metastasis - Li, Yatong; Fan, Yongna; Xie, Yunyi; Li, Limin; Li, Juan; Liu, Jingyi; Jin, Zhengyu; Xue, Huadan; Wang, Zhiwei (Stem cell research & therapy, 2024)
The discovery of embryonic stem cell (ESC) mediating tumoricidal activity revealed the intimate relationship between ESCs and tumor cells, but the functional role of ESCs in tumor progression is poorly understood. To further investigate tumor cell and ESC interactions, we co-cultured mouse ESCs with mouse pancreatic cancer Pan02 cells or mouse melanoma B16-F10 cells in Transwell, and found that tumor cell invasion was significantly inhibited by ESCs. Application of ESCs to tumor-bearing mice resulted in significant inhibition of tumor metastasis in vivo. RNA-Seq analyses of tumor cell and ESC co-cultures identified TP53 and related signalling as major pathways involved in ESC-mediated inhibition of tumor cell invasion and metastasis, which indicated the potential clinical application of ESCs to treat cancer.